Are ill-informed residential water consumers less price-responsive? - Monteiro, H.; Rita Martins; Ramalho, J.J.S.; Ramalho, E.A. (6th World Congress of Environmental and Resource Economists, 2018)
The vast literature estimating residential water demand assumes households are aware of and respond to changes in the tariffs or at least in the average price paid. However, in a framework where consumers face complex tariff schemes, and water bills tend to represent a reduced household expenditure, this awareness cannot be taken by granted. In this paper, we estimate a discrete continuous choice (DCC) model of residential water demand in Portugal that allows price elasticities to change as a function of consumers’ perception of their water bills. A control function approach is added to the DCC model to deal with the potential endogeneity of the perception indicator. We find water demand to be price-inelastic, but less so if consumers’ awareness about the amount they pay is higher. We also provide novel findings on the impact of environmentally-friendly behaviors, rainwater harvesting and availability of alternative water sources.